Integral Education in Institutional Development: Partnership between Islamic Boarding Schools and Alumni - Nadifatul Mufidah; Maskuri Maskuri; Sugeng Listiyo (STAI Hubbulwathan Duri, 2025)
Islamic boarding schools (pesantren) implement an integral education system that combines general and religious knowledge, aiming to produce alumni with both life skills and strong Islamic character. The partnership between pesantren and alumni serves as a key pillar in achieving institutional vision and mission. Alumni, as agents of change, contribute to school advancement, while waqf administrators provide resources for educational development. This study explores the partnership dynamics, its implementation, and its implications for Islamic educational institutions. This research employs a qualitative approach through a case study method. Data were collected through interviews, observations, and document analysis, focusing on the interactions between pesantren, alumni, and waqf administrators. Findings indicate that the partnership model is built upon waqf land, ensuring consistency in institutional goals. Alumni contribute to curriculum development and educational programs, supported by a strong legal framework. The partnership model fosters adaptability and innovation, aligning with contemporary societal needs. The study highlights the importance of alumni involvement in maintaining educational quality and sustainability. The combination of waqf-based resources and alumni-driven initiatives strengthens the institution’s ability to evolve with changing times. The integral education system benefits from this synergy, enhancing both academic and religious learning. The study formalizes the